Developing Animated Video Media Of Indonesian Folktales As An Interactive Learning Tool For Elementary School Students - Paket, Yohana Bunga; Fatmawan, Aditya Ridho; Kurniawati, Kadek Lina (International Journal of Education, Information Technology, and Others, 2025)
This study aims to develop interactive learning media in the form of animated videos of Indonesian folktales as a learning tool for elementary school students. The research used a Research and Development (R&D) approach with the ADDIE model, including analysis, design, development, implementation, and evaluation stages. The analysis was conducted through observations and interviews to identify students’ difficulties in understanding folktale materials. The animated videos were developed using the Canva application, incorporating visuals, narration, music, and animation tailored to the characteristics of sixth-grade students at Nusa Dua Elementary School, Bali. The media was tested with students and teachers to gather feedback and assess its effectiveness. Results showed that the use of animated videos increased students’ interest in learning and improved their ability to comprehend and retell folktales. The media proved to be an effective interactive learning tool that motivates students and facilitates the teaching-learning process. This study contributes to the development of creative and innovative educational media, particularly in language and cultural learning at the elementary level.